Structure, luminescence and scintillation properties of the MgWO4-MgMoO4 system - Mikhailik, V; Kraus, H; Kapustyanyk, V; Panasyuk, M; Prots, Y; Tsybulskyi, V; Vasylechko, L (2008)
The importance of luminescent tungstates and molybdates in several technological applications motivated the study of the structural, luminescence and scintillation properties of the MgWO4-MgMoO4 system. X-ray diffraction studies allowed the identification of three main types of structures in the pseudo-binary MgWO4-MgMoO4 system (sanmartinite β-MgMoO4, cuprosheelite α-MgMoO4, and wolframite MgWO4) and the refinement of the parameters of the crystal lattice. It is found that the single-phase solid solution MgMo 1-xWxO4 with a β-MgMoO4 structure is created only at x<0.10, while for a higher tungsten content a mixture of different phases is formed. The x-ray luminescence spectra of a series of samples of the MgWO4-MgMoO4 system are measured at T = 8 K. The principal emission bands are assigned to the main structural phases as follows: β-MgMoO4, 520 nm; α-MgMoO4, 590 nm; MgWO4 (wolframite), 480 nm. The phase composition of the sample determines the actual shape of the observed spectra. Possible relations between the crystal structure and luminescence properties of different phases are discussed in terms of a configuration coordinate model. Of all the compounds under test, MgWO4 is found to have the best scintillation response for particle excitation (0.90 0.15 that of ZnWO4 at T = 295 K). Further, the light yield also remains high with decreasing temperature, which makes this material potentially useful for cryogenic applications. © 2008 IOP Publishing Ltd.